2021
DOI: 10.4251/wjgo.v13.i12.2129
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E mutant colorectal cancer cells mediate local immunosuppressive microenvironment through exosomal long noncoding RNAs

Abstract: BACKGROUND BRAF V600E mutated colorectal cancer (CRC) is prone to peritoneal and distant lymph node metastasis and this correlates with a poor prognosis. The BRAF V600E mutation is closely related to the formation of an immunosuppressive microenvironment. However, the correlation between BRAF V600E mutation and changes in local immune microenvironment of CRC is not clear. AIM To explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…We would like to point out the complementary findings to this study from previous work that has alluded to other parts of the immune landscape of the tumor microenvironment of BRAF V600E CRC. From this study, Zhi et al [ 1 ] reported a higher level of M2 macrophages in BRAF V600E -mutated patients compared to the wild-type, with no difference in M1 macrophages levels. Yet, the sample number from which these results were obtained was relatively small (BRAF V600E mutation: 10; BRAF wild-type: 20), and this translated to high standard deviations in the M2 counts in both samples.…”
Section: To the Editorsupporting
confidence: 50%
See 2 more Smart Citations
“…We would like to point out the complementary findings to this study from previous work that has alluded to other parts of the immune landscape of the tumor microenvironment of BRAF V600E CRC. From this study, Zhi et al [ 1 ] reported a higher level of M2 macrophages in BRAF V600E -mutated patients compared to the wild-type, with no difference in M1 macrophages levels. Yet, the sample number from which these results were obtained was relatively small (BRAF V600E mutation: 10; BRAF wild-type: 20), and this translated to high standard deviations in the M2 counts in both samples.…”
Section: To the Editorsupporting
confidence: 50%
“…The immune status of the tumor microenvironment is a multilayered complex subject that leads to crucial implications regarding tumor cell immune evasion, therapeutic response or distant invasion tendency. Therefore, we feel that limiting the immune landscape to the levels of tumor-associated macrophages (M1/2) and cancer-associated fibroblasts, as in the study by Zhi et al [ 1 ], would not reflect the whole story. This is particularly due to the fact that other key immune components, such as CD8+ and CD4+ T cells, neutrophils, myeloid-derived suppressor cells and regulatory T cells, were not investigated.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, macrophage M2 polarization was observed in BRAFV600E mutation of CRC, resulting in more angiogenesis and lymphangiogenesis in the microenvironment. Zhi et al believed that this phenomenon may be related to the abundance of some lncRNAs in exosomes ( Zhi et al, 2021 ). As a vital mediator of APC, lncRNA-APC1 directly regulates the stability of Rab5b mRNA, hence reducing the exosome secretion of CRC cells.…”
Section: Biological Roles Of Exosomal Lncrnas In Gastrointestinal Cancermentioning
confidence: 99%
“…BRAF V600E mutation was positively correlated with the expression of TIM3 in both CRC cells and tumor-in ltrating lymphocytes (TILs) (13) as well as the expression of PD-L1 in tumor cells (14), suggesting that it might act as an indicator of ICI treatment e cacy in mismatch repair-de ciency (dMMR) CRC (15). Furthermore, V600E mutation also increased the in ltration of M2 macrophages via promoting microvessels and microlymphatic vessels formation (12).…”
Section: Introductionmentioning
confidence: 99%